Cultural Differences in Back-channeling Contents between English and Kurdish Languages - Qani Nasih Najim; Kawa Qadir Muhammad (Zanco Journal of Humanity Sciences)
In order for a conversation to be communicated more efficiently, participants exchange back-channels as a method of transmitting knowledge to indicate states such as attention, comprehension, misunderstanding, approval and non-acceptance. Listener responses, more commonly referred to as back-channeling, have attracted attention from diverse scholarly disciplines including linguistics because of their importance in effective dialogue and communication. This study introduces back-channeling, conveys its importance, and discusses its implications across Kurdish and English cultures. The study aims at discovering most common Kurdish back-channels through analyzing authentic face-to-face interactions, and identifying their forms and function in conversation. For this purpose, a number of TV channel interviews and programs have been selected to be analyzed as study sample. As a results of this study, it is clearly understood that Kurdish back-channels are quite similar to English ones in having very various types and forms, yet when it comes to functioning in interactions amongst speakers, there are apparent differences in that same forms do not convey same communicative implications. This, undoubtedly, can be attributed to Kurdish and English cross-cultural and language nature differences.